2010
DOI: 10.1111/j.1475-6811.2010.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Why do close partners snoop? Predictors of intrusive behavior in newlywed couples

Abstract: Existing research shows that intrusive behavior has detrimental consequences for relationships. Surprisingly, little is known about why close relationship partners snoop. This study examined why romantic partners engage in intrusive behavior among newlywed couples in the Netherlands. As predicted, the results showed that perceiving a lack of partner disclosure is linked to intrusive behavior, and importantly, that trust moderates this link. Only when people did not trust their partner were their perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 68 publications
(84 reference statements)
2
37
0
Order By: Relevance
“…Parental intrusiveness is more characteristic of mothers who score higher on attachment anxiety (e.g., Adam, Gunnar, & Tanaka, 2004), and low partner disclosure (characteristic of more avoidant people; Mikulincer & Shaver, 2007) predicts intrusiveness (Vinkers et al, 2011) -perhaps to compensate for the partner's distancing behavior. Similarly, in one of our recent studies (Lavy et al, 2010), attachment anxiety was associated with self-reported intrusiveness, and avoidance was associated with perceiving a partner as intrusive.…”
Section: Attachment Insecurities and Intrusivenessmentioning
confidence: 97%
See 2 more Smart Citations
“…Parental intrusiveness is more characteristic of mothers who score higher on attachment anxiety (e.g., Adam, Gunnar, & Tanaka, 2004), and low partner disclosure (characteristic of more avoidant people; Mikulincer & Shaver, 2007) predicts intrusiveness (Vinkers et al, 2011) -perhaps to compensate for the partner's distancing behavior. Similarly, in one of our recent studies (Lavy et al, 2010), attachment anxiety was associated with self-reported intrusiveness, and avoidance was associated with perceiving a partner as intrusive.…”
Section: Attachment Insecurities and Intrusivenessmentioning
confidence: 97%
“…Intrusiveness implies an imbalance between autonomy and relatedness, with one partner compulsively seeking relatedness while disregarding the other person's need for autonomy (Lavy et al, 2010). Intrusiveness includes behaviors such as monitoring and influencing a partner's attitudes and actions, invading a partner's self-boundaries, seeking proximity while lacking sensitivity to a partner's needs (Lavy, Mikulincer, Shaver, & Gillath, 2009), violating a partner's privacy (e.g., Vinkers et al, 2011), and generally being overly dependent and controlling (e.g., Savage, 2000).…”
Section: Intrusiveness In Romantic Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research examining individual’s motives for engaging in “snooping” behavior (e.g., reading partner’s e-mail without permission, searching through partner’s belongings) also found trust to be an important factor. Specifically, individuals who perceived that their partners disclosed less personally relevant information to them were more likely to engage in snooping behavior, especially when they reported lower levels of trust (Vinkers, Finkenauer, & Hawk, 2011). Together, these findings indicate that distrust is an important determinant in experiencing and expressing jealousy.…”
Section: Romantic Jealousymentioning
confidence: 99%
“…Butler (1986) found that partner's desire to control others had a negative effect on trust, and self-esteem had a positive effect on trust. In their study conducted with 188 married individuals, Vinkers, Finkenauer and Hawk (2011) examined the relation between intrusive behavior (checking partner's text messages without his/her permission), trust, and perceived partner disclosure. According to the results of this study, perceiving a lack of partner disclosure is linked to intrusive behavior, and importantly, that trust moderates this link.…”
Section: Dyadic Trust and Burnoutmentioning
confidence: 99%